Effect of Fermentation Time and Concentration of Local Microorganisms (MOL) of Rice Straw on Nitrogen Levels in Cow Biourine - Amin, Muhamad; Dewi, Yuli Kusuma; Jayadi, Edi M (Alpatih Harapan Semesta, 2023)
Biourine is urine taken from livestock, especially ruminants, which is fermented before being used. The purpose of this study was to determine the effective fermentation time and local microorganism concentration (MOL) of rice straw to produce the highest nitrogen content in bovine biourine. Biourine is obtained through the fermentation method and analysis of nitrogen levels using the Kjehdahl method. The fermentation treatment given to bioourine was for 10 and 15 days of treatment using 4 combinations of MOL concentrations of straw, cow urine and EM4 used. The results of the analysis of nitrogen levels in biourine fermented for 15 days were much higher than those fermented for 10 days. The total N levels in biourine fermentation for 15 consecutive days from K1, K2, K3 and K4 were 0.0828%, 0.1110%, 0.1074% and 0.0836%. It can be seen that the highest nitrogen content is at the second concentration with a combination of 50 grams of straw, 1000 mL of cow urine, and 5 mL of EM4. So that the use of the MOL concentration with a fermentation time of 15 days was able to increase total nitrogen levels significantly when compared to control urine which only contained 0.0399% nitrogen if done without fermentation